Language and political psychology: can grammar influence electability? - Tan, Debbita Ai Lin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Daily, the public is plied with political messages from various sources and millions are invested in campaign ads each election year. Yet, surprisingly little is known about the influence of linguistic details in such messages on attitudes about political candidates, especially within the context of Malaysia. The present study is grounded within the structure of framing and grammar, and suggests that grammar can influence attitudes towards a candidate’s electability. The study involved 387 male and female Malaysian university students (19- to 25-year-olds) of various ethnicities. The researcher designed two comprehensive questionnaires based on Fausey and Matlock’s (2011) work. Participants were randomly assigned Version A (n=192) or Version B (n=195) of the questionnaire. Both versions were about the conduct of Members of Parliament, unnamed and without party labels, to avoid bias about actual politicians. The conduct or actions were of negative and positive valence; Version A was framed using the imperfective form [‘was verb + ing’] and employed the modal verb ‘must’, whereas Version B was framed using the perfective form [‘verb + ed’] and employed the modal verb ‘have to’. Primarily, results revealed that imperfective descriptions of negative actions resulted in negative responses to the re-election of a candidate. However, the participants were largely insensitive to grammatical alteration when judging a candidate’s past positive actions. The results on modality demonstrated a preference for the modal verb ‘must’ which carries more “emotional value” than ‘have to’. The present study is novel in that it covers the dimension of modality (which has never been explored in previous studies) and that to date, there is no available research similar to it in the Malaysian context.